Evaluation of rotator cuff muscle strength in healthy individuals - Cortez, Paulo José Oliveira [UNESP]; Tomazini, José Elias [UNESP] (Sociedade Brasileira de Ortopedia e Traumatologia, 2015)
OBJECTIVE: To compare the strength generated by the rotator muscles of the shoulder joint between the right upper limb and left upper limb among healthy individuals. METHODS: To evaluate the muscle strength of upper limbs from isometric contractions in the horizontal direction (rotation) an isometric dynamometer was used, equipped with transducers, signal conditioning, a data acquisition board, and finally, a computer. Study participants were 22 male military subjects, aged between 18 and 19 years old, body mass between 57.7 and 93.0 kg (71.8 ± 9.45 kg) and height between 1.67 and 1.90 m (1.75 ± 0.06 m), healthy and without clinical diseases or any type of orthopedic injury in the muscle skeletal system. RESULTS: The internal rotation in the right upper limb (RUL) was higher than the average strength of internal rotation in the left upper limb (LUL) (p = 0.723). The external rotation strength in RUL was lower than the average strength of external rotation in the LUL (p=0.788). No statistical difference was observed by comparing the strength values of all isometric strength tests. CONCLUSION: For the sample and methodology used to assess muscle strength, there was no statistical difference between the strength generated by the muscles of the rotator cuff of the right and left upper limbs. Experimental Study.
Keywords: Rotator cuff; Shoulder joint; Muscle strength